SLIP WEAKENING, STRAIN AND SHORT-TERM PRESEISMIC DISTURBANCES - Morgounov V.A. (My University, 2004)
The problem of short-term earthquake precursors is discussed. In contrast to the increasing number of reports on short-lived precursors of various types, direct strain measurements cannot detect clearly expressed preseismic anomalies, as follows from the aseismic nucleation mechanism. Based on previously published data and the assumption that the attenuation of the stress-strain field is proportional to r- 3, a possible scenario of the final stage of earthquake nucleation process is proposed on the basis of the slip weakening mechanism in the source and the associated mosaic pattern of precursors on the Earth?s surface. The formulas for estimating the maximum distance of precursor detection and minimum duration of the final stage of inelastic deformation preceding brittle failure of rocks are derived. The data of electromagnetic precursors are interpreted in terms of a skin-layer model. A considerable increase in strain rates at the final stage of the earthquake nucleation provides an opportunity to explain teleseismic effects before strong earthquakes in terms of normalized epicenter distance. The modeling results are compared with in situ observations.